Analisis Tingkat Resiko Gangguan Musculoskeletal Disorder (MSDs) Pada Pekerja Konveksi Sablon Plastik dengan Metode REBA dan OWAS - Mochammad Wachid; Hidayat Hidayat; Yanuar Pandu Negoro (G-Tech: Jurnal Teknologi Terapan, 2024)
Human labor plays a vital role, especially in Manual Material Handling (MMH) processes. While these activities are crucial for smooth operations, they often lead to musculoskeletal disorders (MSDs). MSDs are long-term consequences of improper workstation postures. This research aims to identify the working postures of screen printing workers and propose ergonomic desk designs as improvements. The REBA and OWAS methods can be applied. REBA focuses on assessing the entire body posture of workers, while OWAS aims to identify work activities that potentially cause MSDs. The calculated REBA score is 7, and the OWAS score is 2, indicating a need for preventive measures. The proposed solution is an ergonomic desk design that adjusts to the worker's height.